Focal Choroidal Excavation Complicated by Choroidal Neovascularization - Xu, Haifeng; Zeng, Fanxing; Shi, Depeng; Sun, Xiaolei; Chen, Xiuli; Bai, Yao (Ophthalmology (Rochester, Minn.), 2014)
To evaluate the clinical findings of focal choroidal excavation (FCE) complicated by choroidal neovascularization (CNV). Retrospective, observational case series. Twelve patients (15 eyes) with FCE and CNV. The medical records of the patients were reviewed. Clinical findings including age, sex, refraction, color photography, fundus fluorescein angiography (FFA), indocyanine green angiography (ICGA), and spectral-domain optical coherence tomography (OCT) were analyzed. Fundus fluorescein angiography, ICGA, and OCT findings. The 12 patients included 6 women and 6 men. The mean age was 46.8±13.4 years (range, 26-64 years). One half of the patients were emmetropic, and the others were myopic (−0.5 to −3.0 diopters). All subjects were Chinese. Before CNV development, normal appearance or nonspecific pigment disturbance could be seen around the choroidal excavation. Corresponding to the excavation, window defects were observed by FFA, whereas hypofluorescence was found on ICGA images. Choroidal neovascularization in all eyes was classic as revealed by FFA. The OCT images showed that all eyes had a single choroidal excavation. In 7 of the 15 eyes, the choroidal excavation was located subfoveally, and in the other 8 eyes, it was eccentric. All CNV lesions grew from the bottom or slope of the excavation. Three patients had bilateral involvement. Choroidal neovascularization occurred in both conforming and nonconforming type FCEs, regardless of whether the excavation was shallow or deep, subfoveal or eccentric. All CNV lesions responded well to intravitreal injection of anti–vascular endothelial growth factor (VEGF) agents. After a single injection, CNV regressed in 13 of 15 eyes. Two eyes received an additional injection. Nonconforming FCE changed to the conforming type after successful treatment of CNV. Focal choroidal excavation is not always stable. Choroidal neovascularization commonly can be seen in patients with FCE and responds well to intravitreal anti-VEGF agents.